Barriers to reporting postpartum hemorrhage at different levels of healthcare facilities in Nigeria: A qualitative study - Sirajo Mohammed; Lee Khuan; Ruth Packiavathy Rajen Durai; Irmi Zarina Binti Ismail; Saleh Ngaski Garba (Belitung Nursing Journal, 2022)
Background: Maternal mortality reduction remains a world health priority. One of the causes of maternal death is bleeding after childbirth. However, little is known regarding barriers to reporting for postpartum hemorrhage care among postnatal women in Nigeria. Objective: This research aimed to understand the perceived barriers to reporting postpartum hemorrhage care experienced by women and healthcare workers in Birnin Kebbi, North west-Nigeria. Methods: Qualitative case research was employed in this study with face-to-face interviews among ten postnatal women who experienced bleeding and six healthcare workers. Data were collected from September to November 2021. The interviews were all audio-taped, transcribed verbatim, and analyzed using thematic analysis. NVivo Pro Version 12 was applied to organize further and manage the data. Results: Six themes were developed: (1) knowledge deficit, (2) poor attitudes, behaviors, and performances, (3) low socioeconomic status, (4) lack of healthcare personnel, (5) cultural norms, and (6) lack of access to healthcare facilities. Conclusion: The study findings might serve as input for healthcare policymakers and healthcare workers to improve health and reduce maternal mortality. Enhancing knowledge and awareness about reporting process is necessary to improve reporting for postpartum hemorrhage care among women. Training and continuous professional development of health care workers are also highly suggested to enhance the quality of care.